INVESTIGATING SPIRITUALITY AND MATERIALISM IN AN IT-BASED COMPANY - Arini, Dinda; Pratama, Andika Putra (Journal of Business and Management, 2018)
Abstract. The information and technology systems or simply said as IT take a big part of peoples in the daily activities. One of IT development company is through CV DST. Based on the preliminary study, CV DST is facing problems at human resources where the managers (board lines) do not understand the appropriate ways to approach their employees. Later on, the managers focus on the material facilities of their employees and not really pay attention to the spiritual facilities. After that, there is an issue occur that said if the employees are not motivate enough to do their job. The purpose of this research is to analyze the dominant psychological disposition of CV DST employees‘ which is spirituality or materialism based on their profiles and how it reflected in employees‘ behavior to be relevant on the business environment and support the organization to reach the goals. Psychological disposition analysis is done by doing quantitative approach that includes of distributed questionnaire. Then, in order to analyze the psychological dispositions related to self-perceived motivation, self-perceived performance, self-perceived satisfaction and self-perceived engagement is done by doing qualitative approach which is in-depth interview. The result of psychological analysis describes that spirituality have dominant position compared to materialism. However, this result still has to consider additional information such as employees‘ age so it can get the details of employees‘ psychological disposition distribution. If it‘s related to self-perceived motivation, self-perceived performance, self-perceived satisfaction and self-perceived engagement known that employees want to get more attention in their spiritual things. So, this research can solve the existing problems to get the optimal motivation, performance, satisfaction, and engagement of CV DST employees‘.Keywords: Psychological Disposition, Motivation, Performance,Satisfaction